A Naturalistic Observation of Spontaneous Touches to the Body and Environment in the First 2 Months of Life - DiMercurio, Abigail; Connell, John P.; Clark, Matthew; Corbetta, Daniela (Frontiers in Psychology, 2018)
Self-generated touches to the body or supporting surface are considered important contributors to the emergence of an early sense of the body and self in infancy. Both are critical for the formation of later goal-directed actions. Very few studies have examined in detail the development of these early spontaneous touches during the first months of life. In this study, we followed weekly four infants in two naturalistic 5-min sessions (baseline and toys-in-view) as they laid alert in supine from the age of 3 weeks until they acquired head control. We found that throughout the 2 months of observation, infants engaged in a high rate of touch and spent about 50% of the time moving their hands from one touch location to the next. On most sessions, they produced up to 200 body/surface contacts and touched as many as 18 different areas (mainly upper body and floor) both hands combined. When we did not consider the specific areas touched, the rates of touches were higher to the body than to the floor, but the duration of contacts and the most touched areas were higher for the supporting surface than for the body. Until the age of 9 weeks, we found no consistent differences in the rate of touch between head and trunk. Infants also did not display significant differences in their rate of touch between right and left hand or between conditions. However, we discovered that in the earlier weeks, infants engaged more often in what we called “complex touches.” Complex touches were touches performed across several body/floor areas in one continuous bout while the hand maintained contact with the body or floor. Single touches, in contrast, corresponded to one touch to one single body or floor area at a time. We suggest that infants are active explorers of their own body and peripersonal space from day 1 and that these early self-generated and deeply embodied sensorimotor experiences form the critical foundation from which future behaviors develop.